Towards the Egyptian Charter for Conservation of Cultural Heritages - Corinna Rossi; Sara Rabie (Journal of Contemporary Urban Affairs, 2021)
The notion of “Cultural heritage” is quite modern compared to other humanistic fields developed in the last century. Conservation as a science has emerged and took shape during international conventions and treaties in many places in Europe and developed various frameworks to recognize the heritage and its value but based on “Eurocentric bias” criteria. The fact of sharing universal values and common practices during the age of globalization had a significant impact on conservation actions in contexts utterly different from western societies and don’t share the same historical or cultural dimensions. Therefore, this study traces the history of the evolution of conservation in the west from two perspectives; the historical one and the developing methodologies, and the philosophies behind the main theories in conservation. Cultural heritage is a reflection of the identity of the society and its past; thus, this study outlines the development of conservation practices in Egypt within the international approaches in a chronological order to investigate the social response and the impact of the political and cultural influence of the cultural consciousness of the society and the conservation actions in the Egyptian context. Furthermore, to investigate the contribution of international charters in developing national policies in Egypt.